DIGITAL DEMENTIA IN CHILDREN AND ADOLESCENTS: SYMPTOMS, RISK FACTORS AND PREVENTION STRATEGIES. A NARRATIVE REVIEW - Felisiak, Patrycja; Barszczewska, Magdalena; Bieszczad, Dominika; Botto, Zofia; Kowalczyk, Dominika; Krystek, Klaudia; Reizer, Barbara; Swójnóg, Marzena; Ślazyk , Dominik Andrzej; Śliwa, Zofia (International Journal of Innovative Technologies in Social Science, 2026)
Children and adolescents, as the new generation of avid technology users, are often able to use it to their great benefit. However, it comes with the cost of being exposed to a variety of health risks, cognitive health being one of the main areas affected. As developing brains are the most susceptible to these risks, Manfred Spitzer’s concept of digital dementia seems as relevant as ever nowadays.In the present study, we analyse over a hundred published works with the goal of creating a compact yet comprehensive summary of existing knowledge on digital dementia in the population of infants, preschoolers, schoolchildren and adolescents.Findings suggest that multiple cognition areas are affected, with memory, critical thinking and problem solving being among the most alarming. While the role of parents as guardians of digital health cannot be overstated, other factors such as environment and unmodifiable traits also play a role. For preventing and mitigating this problem, a collaborative effort of caretakers but also teachers, doctors and policy makers is most urgently needed.We conclude that digital dementia among youth is a common problem, therefore recognising symptoms early, minimising risks and preventing its progression will prove beneficial to whole generations.